South Asian security and international nuclear order creating a robust indo-Pakistan nuclear arms control regime - Carranza, Mario Esteban (Routledge Ashgate, 2009)
Mario Carranza studies in depth the linkages between Indo-Pakistani nuclear relations and the International Nuclear Order. He critically analyzes the de facto recognition by the United States of India and Pakistan as nuclear weapon states and looks at the impact of that recognition on the International Nuclear Order and its linchpin, the Nuclear Non-Proliferation Treaty (NPT). The book provides a critical analysis of the New International Nuclear Order sponsored by the United States after the September 11 terrorist attacks and the place of India and Pakistan in that order. The author considers the survival of India and Pakistan in relation to a strategy of nuclear deterrence and debates the possibility of establishing a robust nuclear arms control regime in South Asia as part of a broader effort to revive global nuclear arms control and disarmament negotiations.